Sedimentary and evolutionary cycles. - Edited by Ulf Bayer and and Adolf Seilacher (Springer Verlag, 1985)
Outcome of a Symposium held at Tubingen Sept. 15-17, 1983 sponsored by DFG and the Sonder-forschungerbereich 53'--Pref.